Empowering Doctoral Candidates in Finding Relevant Concepts in a Literature Set - Dreher, Naomi; Dreher, Heinz (the Informing Science Institute, 2011)
Research activity connects prior findings with new and emerging ideas in the hope of attracting attention of those in the community who are able to make some sort of profit from the application of those ideas. Finding relevant concepts from among the vast repository of already published ideas is an important challenge for all researchers. Nowadays, there is ample opportunity to take advantage of the empowering aspects of developments in information technology. In this study, we share some ideas to efficiently and effectively find relevant concepts in a given literature set. Our need was to find and tag predetermined concepts from among the scores of research articles that our literature search had delivered – necessarily this was a large enough task to warrant the development of some automated support to find and tag the relevant concepts. We had prior exposure to Adobe® Acrobat® Pro and noted that it provides superior ‘search and find’ facilities; we decided to trial this use for our purposes in the ‘Tribes and Cultures’ research project. We have devised and trialled a seven step, semi-automated method to assist in finding relevant concepts from within collections of research articles, retrieved as Portable Document Format (PDF) files, from bibliographic databases and digital libraries.